Fiscal crises in the developing world: Zooming out and zooming in on Brazil's public finance history - Rogrigo Cantu (economic sociology. perspectives and conversations, 2024)
Fiscal crises are a central theme in the recent history of many emerging economies, as they are more vulnerable to budget distress than developed countries. From 1970 to 2015, emerging markets experienced more than twice as many fiscal crises as their wealthier counterparts (Gerling et al. 2017, 13). Of the scholarship dedicated to understanding this theme, mainstream economics has made commendable efforts. [...] Sociology can offer fresh and more comprehensive perspectives on fiscal crises. What are their causes and consequences, not just from an economic standpoint but also from a sociopolitical one?
Keywords: 300